Ce qui reste : enquête et écriture sur un territoire marginal - Magdalena Brand (Glad!)
This article questions the passage between the survey and the text from the point of view of the issue of traces and the loss. What is the loss in the ethnographic text? Of which reality the ethnographic text can be the trace? The article questions the process of writing on an ethnographic survey conducted in Bangui on a neighborhood of Central African women who worked as waitresses and prostitutes for French expatriates. Through three social, memorial and mythical figures encountered during the investigation, the article questions the limits of ethnographic writing to transmit in the academic context the daily lives of women, to remember and recognize what made the value of their lives.